2021
DOI: 10.1038/s41370-021-00299-4
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to chemical components of fine particulate matter and ozone, and placenta-mediated pregnancy complications in Tokyo: a register-based study

Abstract: Background Maternal exposure to fine particulate matter (PM2.5) was associated with pregnancy complications. However, we still lack comprehensive evidence regarding which specific chemical components of PM2.5 are more harmful for maternal and foetal health. Objective We focused on exposure over the first trimester (0–13 weeks of gestation), which includes the early placentation period, and investigated whether PM2.5 and its components were associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Significant associations were also found between increased the risk of pre-eclampsia and the second trimester exposure of BC in a cohort study involving 228,438 births in the United States; 22 however, another cohort study involving 83,454 Japanese women showed that exposure to the carboncontaining components of PM 2.5 in the first trimester was positively associated with placenta-mediated pregnancy complications (such as pre-eclampsia). 38 The second trimester was a sensitive window for BC exposure, possibly because maternal plasma volume increased with the steepest increase occurring during the second trimester, and body load for pregnant women increases. 39 BC is mainly emitted from the incomplete combustion process of biomass and fossil fuels.…”
Section: Discussionmentioning
confidence: 99%
“…Significant associations were also found between increased the risk of pre-eclampsia and the second trimester exposure of BC in a cohort study involving 228,438 births in the United States; 22 however, another cohort study involving 83,454 Japanese women showed that exposure to the carboncontaining components of PM 2.5 in the first trimester was positively associated with placenta-mediated pregnancy complications (such as pre-eclampsia). 38 The second trimester was a sensitive window for BC exposure, possibly because maternal plasma volume increased with the steepest increase occurring during the second trimester, and body load for pregnant women increases. 39 BC is mainly emitted from the incomplete combustion process of biomass and fossil fuels.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 19 , 27 , 35 , 36 The method we used to assess individual O 3 exposure outperformed previous exposure assessment methods in terms of exposure accuracy, which may also account for the differences in the results. 18 , 19 , 35 …”
Section: Discussionmentioning
confidence: 99%
“… 16 A retrospective case-control study in the US and a registry-based study in Japan showed similar associations between maternal O 3 exposure and HDP risk. 17 , 18 In contrast, some studies from South Korea and China did not show an association of O 3 exposure with HDP risk. 19 , 20 This inconsistency may be due to different populations, different exposure assessment approaches, unadjusted residual confounders, selection bias, or the levels of O 3 pollution across study areas.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Identifying critical exposure windows would allow for the design of targeted prevention strategies, as well as the exploration of the potential biological mechanisms underlying the associations of PM 2.5 exposure with PTB. In previous research evaluating the effect of gestational PM 2.5 exposure on pregnancy complications of placental origin, the critical window was identified as the first trimester ( 34 ). In this study, PM 2.5 exposure during the second trimester demonstrated significant associations with PTB, which is consistent with some previous epidemiological studies ( 35 37 ), whereas other studies identified the late stage of pregnancy as the most significant critical window ( 19 , 20 , 38 ).…”
Section: Discussionmentioning
confidence: 99%